The importance of external financing in management of innovative processes in the SME sector - Kokot-Stępień, Patrycja (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: A broad approach to the SME sector causes that small and medium-sized enterprises are active in all segments of the economy. Each segment is characterized by a certain way of doing a business and thus financing it. Therefore, an important issue for the small and medium-sized entities is to provide both liquidity and continuity of financing and access to such sources of financing that will allow the implementation of innovative projects since innovation affects the pace and direction of development of the specific economic entity as well as significantly indicates the forms and structure of business cooperation. Aim: The aim of the article is to analyze the extent to which the various sources of financing are used by small and medium-sized enterprises in the implementation of innovative projects, and to show the relationship between external sources of financing and the level of expenditure on innovation of SMEs in Poland. Results: The analysis was based on examining the dependence of the scale of innovative activity of enterprises in the SME sector in Poland on the possibility of using not only own funds, but also funds from external sources, the use of which by small and medium-sized enterprises is still too low and is often limited to EU funds.